2002
DOI: 10.2105/ajph.92.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Bar and Club Tobacco Promotions in the Alternative Press: Targeting Young Adults

Abstract: Objectives. This study examined changes in tobacco promotions in the alternative press in San Francisco and Philadelphia from 1994 to 1999. Methods. A random sample of alternative newspapers was analyzed, and a content analysis was conducted. Results. Between 1994 and 1999, numbers of tobacco advertisements increased from 8 to 337 in San Francisco and from 8 to 351 in Philadelphia. Product advertisements represented only 45% to 50% of the total; the remaining advertisements were entertainment-focused promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 14 publications
0
59
0
1
Order By: Relevance
“…10---12 Since the 1998 Master Settlement Agreement put forth restrictions on tobacco industry marketing to youths, 13 young adults have become an increasingly important target audience. 14,15 This is evident in the data, as approximately 20% of young adults still smoke cigarettes, 16 and recent national data show that young adults aged 18 to 25 years had the highest prevalence of current tobacco use (40.8%) compared with youths (ages 12---17 years) or adults (ages 26 years and older). 17 Use of certain noncigarette products are particularly high; for example, data from a nationally representative sample found that 30% of young adults aged 18 to 34 years had ever used cigars; 26% had used little cigars, cigarillos, or bidis; and 18% had used a hookah.…”
mentioning
confidence: 89%
“…10---12 Since the 1998 Master Settlement Agreement put forth restrictions on tobacco industry marketing to youths, 13 young adults have become an increasingly important target audience. 14,15 This is evident in the data, as approximately 20% of young adults still smoke cigarettes, 16 and recent national data show that young adults aged 18 to 25 years had the highest prevalence of current tobacco use (40.8%) compared with youths (ages 12---17 years) or adults (ages 26 years and older). 17 Use of certain noncigarette products are particularly high; for example, data from a nationally representative sample found that 30% of young adults aged 18 to 34 years had ever used cigars; 26% had used little cigars, cigarillos, or bidis; and 18% had used a hookah.…”
mentioning
confidence: 89%
“…Los programas de intervención en adultos jóvenes tienen una especial prioridad, ya que la transición a la edad adulta en diversas poblaciones está marcada por el deterioro de algunos comportamientos saludables los cuales pueden permanecer durante el resto de la vida adulta [13][14][15] .…”
Section: Introductionunclassified
“…For example, studies strongly suggest that increases in smoking prevalence for women of all ages in the 1970s were related to the targeted marketing strategies employed by Philip Morris (e.g., Virginia Slims [11][12][13]), and the Joe Camel campaign was related to an increase in adolescent smoking (22)(23)(24). Therefore, the increasing trends in young adult smoking onset reported here for both African Americans and non-Hispanic Whites suggest that young adult populations may have been increasingly targeted by the tobacco industry for quite some time (25,26).…”
Section: Tobacco Industry Targeting Of Adultsmentioning
confidence: 69%